THE INFLUENCE OF SERVICE QUALITY ON CUSTOMER LOYALTY MEDIATED BY BRAND TRUST - Tumpal JRSitinjak; Abdullah Rakhman; Toni Sitinjak; Brastoro Brastoro; Bernadine Bernadine (International Journal of Social Science, 2022)
This research aims to analyze the influence of Service Quality, Brand Trust, and Loyalty of Starbucks customers. Through this research, the researcher can find out the magnitude of influence that occur on customer loyalty. Based on the purpose of this research, the hypotheses are; H1: Service quality influences on brand trust; H2: Service quality influences on customer loyalty; and H3: Brand trust influences on customer loyalty. Judgmental sampling is non-probability sampling technique that has been used for this research. The data was gathered through the communication method as the data are collected from 100 respondents by distributed questionnaire and for essential measurements using Likert Scale. The research method was validated through construct validity and reliability test, and for hypotheses test Structural Equation Model (SEM) analysis was used. The result of this research indicates that service quality significantly influences toward brand trust. Service quality doesn’t influence toward customer loyalty. Then, brand trust also doesn’t influence toward customer loyalty. After the processes conducted in this research, it can be concluded that only service quality give positive influence to brand trust in Starbuck. For the sugestion, much better if there is availability to give any feedback, the purpose is to know about lacks of Starbucks